Effects of the Irrigation Modernization in Spain 2002–2015 - Berbel, Julio; Expósito-García, Alfonso; Gutierrez-Martín, Carlos; Mateos, Luciano (Springer Nature, 2019)
Regions and basins suffering from water scarcity have promoted the modernization of irrigation systems, defined as irrigation efficiency enhancement as a measure for the adaptation to a growing demand and a limited supply of water resources. In the period 2002–2015, Spain carried out an intense irrigation modernization process with the aim of achieving significant water savings and higher flexibility and to guarantee supply, among other favourable outcomes (e.g. environmental and socio-economic). Nevertheless, certain unfavourable effects of irrigation modernization also need to be discussed. This study analyses these effects in Spain based upon a DPSIR (Driving forces, Pressures, States, Impacts, and Responses) framework and a wideranging review of the existing empirical literature. Our findings are highly relevant to inform decision-makers in the planning of future irrigation modernization programmes worldwide.
Keywords: Riego - España - 2002-2015; Irrigation modernization; Water conservation; Water use; Rebound effect; Water management